Immunosuppressive therapy (IST) in adult patients with acquired aplastic anemia (AA): A single‐center experience over the past 15 years. (21st May 2019) - Alashkar, Ferras; Oelmüller, Maren; Herich‐Terhürne, Dörte; Turki, Amin T.; Schmitz, Christine; Vance, Colin; Dührsen, Ulrich; Röth, Alexander
Abstract: Objective: Immunosuppressive therapy (IST) with horse anti‐thymocyte globulin (hATG) and cyclosporine (CsA) is considered one of the first‐line therapies in patients (pts) with acquired aplastic anemia (AA). Methods: In our single‐center, retrospective analysis response rates (RRs) to ATG/CsA at a minimum of 6 mo were evaluated in 67 treatment‐naïve (TN) AA pts (52.2% (35/67) females; median age 45 y (range 18‐89 y)) being treated at the West German Cancer Center at the Department of Hematology at the University Hospital of Essen between April 2000 and December 2015. Results: Overall 6 mo RRs in TN pts following ATG/CsA were 67.2% (45/67) (5‐year OS: 79.5%). In TN hATG‐treated pts 6 mo RRs were 75.5% (37/49) (5‐year OS: 81%) compared to 44.4% (8/18) (5‐year OS 73.5%) following rabbit ATG (rATG). Response to ATG/CsA was dependent of age, absolute reticulocyte count (ARC), and disease severity. Six mo RRs to salvage ATG/CsA in relapsed/refractory (R/R) pts were 37.5% (6/16). Conclusion: Our data independently confirm the findings of previous studies that hATG/CsA is superior to rATG/CsA in TN pts. The lack of hATG availability should not result in abstaining it from an indicated ATG therapy, even though ATGAM ® is not registered in Germany.